Development of General Chemistry Teaching Materials Using the PjBL-STEM Model to Enhance Students' Creative Thinking Skills - Purba, Jamalum; Panggabean, Freddy Tua Musa; Sutiani, Ani (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2024)
Thinking creatively is a crucial higher-order skill that students must acquire when they graduate from university. This necessitates lecturers designing and developing learning processes that actively engage students while fostering their creative thinking abilities. This study aims to develop and validate general chemistry teaching materials on organic compounds and reactions using the PjBL-STEM model and evaluate their effectiveness in improving students' creative thinking skills. The study employed the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model. The teaching materials were designed as comprehensive books that adhered to the PjBL-STEM framework. Effectiveness was measured by analyzing improvements in students’ creative thinking abilities through quantitative testing. The results demonstrate that the PjBL-STEM-based teaching materials are valid and feasible for implementation. Their effectiveness in enhancing students' creative thinking abilities was statistically significant (t-count = 32.488; p = 0.000), with an average improvement of 42.725 ± 8.317. The development of PjBL-STEM-based teaching materials offers a valuable tool for chemistry education, effectively promoting creative thinking skills among students. This approach provides a practical framework for lecturers to design innovative, student-centered learning strategies.